Addition of Carrot Paste (Daucus carota L.) to the Physical Characteristics of Mochi - Siti Afina Sabrina; Dewi Nur Azizah; Ana Nadiya Afinatul Fishi (Indonesian Journal of Food Technology, 2023)
Mochi is a cake with a chewy and soft texture made from glutinous rice flour and contains peanuts. This sticky rice flour causes the color of the mochi to turn milky white. This can be corrected by adding natural dyes to make the appearance of mochi more attractive. Carrots can be used as natural dyes in making mochi, indirectly the mochi produced becomes healthier and more nutritious. This study aims to determine the physical characteristics of mochi with the addition of carrot paste and find out the right formulation in adding carrot paste to mochi that is liked by the panelists. This research method used an experimental method with a randomized block design (RBD) 1 factorial, namely the addition of carrot paste concentrations of 0%, 25%, 50%, 75%, and 100%. The results showed that the mochi produced had an overall appearance that was quite flour-coated and the shape was less uniform, pale orange in color, typical flour aroma, chewy, and sweet in taste. The best results most preferred by the panelists in this study were obtained through analysis of physical characteristics, namely the treatment of adding 25% carrot paste concentration with an overall appearance value of 4.00, color 3.87, aroma 3.80, elasticity 3.67, and taste 3 ,93.